Effect of pupil dilation on biometry measurements and intraocular lens power in eyes with high myopia - Xi, Wenqun; Yang, Mingmin; Wan, Jinci; Wang, Yuan; Qiao, Yuanjiao; Huang, Xiaosheng; Liu, Xinhua; Fan, Ning; Liu, Shenwen; Zeng, Kun; Chen, Sheng (Frontiers in Medicine, 2022)
Purpose: The present study sought to evaluate the effects of pupil dilation on ocular parameter measurements and intraocular lens (IOL) power calculation using IOLMaster in highly myopic cataract patients. Methods: A total of 233 eyes were included in this prospective study and assigned to four groups based on range of axial length (AL) as follows: group A:26-28 mm, group B:28-30 mm, group C:30-32 mm, and group D:32-36 mm. Flattest and steepest keratometry (K1 and K2), AL, anterior chamber depth (ACD), lens thickness (LT) and white-to-white (WtW) were determined using IOLMaster before and after administration of topical tropicamide. The corresponding IOL powers were calculated using Sanders–Retzlaff–Kraff/theoretical (SRK/T), Haigis and Barrett Universal II formulas. Results: Variations in AL, K1 and K2 following dilation were not significant (P>0.05 in all groups). The results showed that ACD increased significantly after dilation (P=0.000 in all groups), whereas LT decreased significantly after dilation (P=0.000, 0.000, 0.001, 0.003). Post-dilation WtW increased significantly in Group A, B and C (P=0.001, 0.001, 0.025) but not in Group D. When IOL power was calculated as a discrete variable, significant differences were observed between pre- and post-dilation IOL power. Conclusions: Pupil dilation in cataract eyes with high myopia does not cause significant changes in AL and K. However, it significantly increases ACD as well as WTW values and significantly decreases the LT value. Surgeons should evaluate the effect of pupil dilation on IOL power prediction as the present findings show extreme cases. Notably, Barrett Universal II formula had the best concordance between different pupil conditions in long eyes.